Association of Socioeconomic Status With Relapse After Ponseti Method Treatment of Idiopathic Clubfeet. Issue 3 (August 2022) - Akinyoola, Lawrence A.; Gunderson, Zachary; Sun, Seungyup; Fitzgerald, Ryan; Caltoum, Christine B.; Christman, Tyler W.; Bielski, Robert; Loder, Randall T.
Background: The Ponseti method is today's standard treatment of idiopathic talipes equinovarus (ITEV). Compliance with foot abduction bracing (FABO) and socioeconomic factors have been shown to impact treatment outcome. We wished to further study socioeconomic factors using the Area Deprivation Index (ADI), a more comprehensive way to evaluate socioeconomic status, which has not been done before. Methods: All TEV patients from 2010 through 2019 treated with the Ponseti method were reviewed. Standard demographic variables, as well as the number of casts to complete initial correction, FABO compliance, and occurrence of relapse were tabulated. Socioeconomic level was quantified with the 2018 ADI. Results: There were 168 children; 151 had typical and 17 complex TEV. Average follow-up was 4.3 ± 1.8 years; relapse occurred in 46%. There were no significant differences in the percentage of relapse by sex, race, or ADI. FABO noncompliance was present in 46%. Relapse increased with increasing time of follow-up and FABO noncompliance (76% vs 21%, P < 10 −6 ). Multivariate logistic regression analysis revealed that only FABO compliance and length of follow-up were associated with relapse. The OR of relapse for FABO noncompliance was 17.9 (7.6, 42.4, P < 10 –6 ) and for follow-up >4 years the OR was 4.97 (2.1, 11.70, P = .0003). Conclusion: The outcome of the Ponseti method for TEV treatment is dependent on local circumstances. In our state, socioeconomic status, as determined by the ADI, was not associated with the occurrence of relapse. Thus, each center needs to assess its results, and analyze its own reasons for relapse. There were no other demographic variables associated with relapse except FABO compliance and length of follow-up. Parents should be strongly advised that FABO compliance and follow-up appears paramount to achieving the best results, and that complex TEV are at greater risk for relapse. Level of Evidence: Level IV, case series